Recruitment-related information sources and organizational attractiveness: Can something be done about negative publicity? - VAN HOYE, Greet (Institutional Knowledge at Singapore Management University, 2005)
The present study begins to fill a gap in the recruitment literature by investigating whether the effects of negative publicity on organizational attractiveness can be mitigated by recruitment advertising and positive word-of-mouth. The accessibility-diagnosticity model was used as a theoretical framework to formulate predictions about the effects of these recruitment-related information sources. A mixed 2 x 2 experimental design was applied to examine whether initial assessments of organizational attractiveness based on negative publicity would improve at a second evaluation after exposure to a second, more positive information source. We found that both recruitment advertising and word-of-mouth improved organizational attractiveness, but word-of-mouth was perceived as a more credible information source. Self-monitoring did not moderate the impact of information source on organizational attractiveness.